2019
DOI: 10.1186/s13046-019-1497-0
|View full text |Cite
|
Sign up to set email alerts
|

Triple blockade of EGFR, MEK and PD-L1 has antitumor activity in colorectal cancer models with constitutive activation of MAPK signaling and PD-L1 overexpression

Abstract: Background: Molecular mechanisms driving acquired resistance to anti-EGFR therapies in metastatic colorectal cancer (mCRC) are complex but generally involve the activation of the downstream RAS-RAF-MEK-MAPK pathway. Nevertheless, even if inhibition of EGFR and MEK could be a strategy for overcoming anti-EGFR resistance, its use is limited by the development of MEK inhibitor (MEKi) resistance. Methods: We have generated in vitro and in vivo different CRC models in order to underline the mechanisms of MEKi resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Some examples are the inhibitors of Axl (NCT03184558), VEGFR (NCT03394287, NCT03797326) and c-Kit (NCT03855358). Furthermore, there is a rapid increase of the number of studies showing the efficacy of co-blocking PD-1, or its ligand, and RTKs in various human cancers [14][15][16][17], including TNBC [18].…”
Section: Introductionmentioning
confidence: 99%
“…Some examples are the inhibitors of Axl (NCT03184558), VEGFR (NCT03394287, NCT03797326) and c-Kit (NCT03855358). Furthermore, there is a rapid increase of the number of studies showing the efficacy of co-blocking PD-1, or its ligand, and RTKs in various human cancers [14][15][16][17], including TNBC [18].…”
Section: Introductionmentioning
confidence: 99%
“…It is of great clinical signi cance to study its expression in colorectal cancer for its pathogenesis and future treatment. In colorectal cancer, there are a few inconsistencies in the prognosis of PD-L1 [32,33] . Our data showed that PD-L1 expression was signi cantly higher in d-MMR patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interaction of PD-1 and PD-L1 inhibits T-cell activation and cytokine production. PD-L1 is induced by many cytokines, such as interferon-γ (IFN-γ), signal transducer and activator of transcription 3 (STAT3), epidermal growth factor receptor (EGFR), transforming growth factor β (TGFβ), and hypoxia inducible-factor-1α (HIF-1α) [10] . In normal immune system, PD-1/PD-L1 pathway activation will inhibit the immune function of T lymphocytes and promote the inhibitory function of regulatory T cells, which can reduce the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples are the inhibitors of Axl (NCT03184558), VEGFR (NCT03394287, NCT03797326) and c-Kit (NCT03855358). Furthermore, there is a rapid increase of the number of studies showing the e cacy of co-blocking PD-1, or its ligand, and RTKs in various human cancers [14][15][16][17], including TNBC [18].…”
Section: Introductionmentioning
confidence: 99%